Foamy macrophages in atherosclerosis: unraveling the balance between pro- and anti-inflammatory roles in disease progression - Ijaz, Adil; Yarlagadda, Bhavya; Orecchioni, Marco (Frontiers in Cardiovascular Medicine, 2025)
Atherosclerosis is a complex immuno-metabolic disease characterized by lipid accumulation and chronic inflammation within arterial walls, leading to cardiovascular events such as stroke and myocardial infarction. Central to the disease are arterial plaques initiated by modified low-density lipoproteins (LDL), particularly oxidized LDL, deposited in the arterial intima. This deposition activates tissue-resident macrophages (TRMs), inducing a lipid-loaded “foamy” phenotype. Additionally, endothelial dysfunction promotes monocyte recruitment, differentiation into macrophages, and further foam cell formation. Foamy macrophages were initially identified as anti-inflammatory but have recently shown dual functionality, possibly depending on the disease stage and phenotype. Recent mouse and human studies also identified subsets of “foamy” macrophages with both pro and anti-inflammatory features. This review examines “foamy” macrophage complex roles and phenotypic diversity in atherosclerosis, emphasizing their potential as therapeutic targets to reduce inflammation and slow disease progression.